PENGARUH KESEHATAN, KESELAMATAN, DAN KEAMANAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERUSAHAAN LISTRIK NEGARA (PLN) WILAYAH SULUTTENGGO AREA PALU - Muhammad, Abdul Jawad (Katalogis, 2017)
The research intends to determine simultaneous and partial influence of health, safety, and job security on the performance of employees at The National Electricity Company in The Area of Suluttenggo Palu. Type of research is correlational. Population involves 90 employees at The National Electricity Company in The Area of Suluttenggo Palu. Data collected by questionnaire, documentation, interview, and observation. Type of data is qualitative and quantitative taken from primary and secondary sources. Method of analysis is multiple regression analysis. Based on the test result, it is shown that health, safety, and job security simultaneously and partially have positive and significant influence on the performance of employees at The National Electricity Company in The Area of Suluttenggo Palu.